Beacon Aided Positioning Method for Lunar Probes Using Temporal Interferometry. (30th March 2022) - Liu, Yang
Abstract : With a series of complex lunar exploration missions carried out, reliable autonomous navigation approaches for lunar probes are in demand. In this paper, aiming to obtain the position of the probes with high accuracy and computational efficiency, a novel passive positioning scheme for lunar probes is presented. We first designed a reference system including four beacons with known positions. Then, we proposed arctangent temporal interferometry (ATI) method for ambiguity resolution in displacement measurement. Moreover, the quad-beacon displacement search (QBDS) algorithm is proposed for 2-dimension (2D) position search, which enables accurate and computational-efficient 2D positioning for lunar probes. The simulation validations show the effectiveness of the proposed positioning scheme and algorithms.